2022
DOI: 10.1002/admi.202201248
|View full text |Cite
|
Sign up to set email alerts
|

Moving Contact Line Instability on Soluble Fibers

Abstract: This paper presents a new kind of instability when inserting a soluble fiber into liquid. After wetting and dissolving the fiber by the liquid, the moving contact line (MCL) spontaneously loses stability. Because the sculpted shape of the fiber looks like a Chinese pagoda, this instability is named as the pagoda instability (PI). The coupling of dissolution and wetting leads to other special phenomena, i.e., dissolving‐induced jet flow, and optimizes the fiber shape, etc. A criterion of PI is proposed and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…19,21,50 Therefore, accurately judging the optimized shape is of great significance. It is noteworthy that the tip apex curvature radius cannot be infinitesimal, but that theoretical works 16–18 assume the apex to be infinitely sharp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…19,21,50 Therefore, accurately judging the optimized shape is of great significance. It is noteworthy that the tip apex curvature radius cannot be infinitesimal, but that theoretical works 16–18 assume the apex to be infinitely sharp.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, an optimized tip can be cut and glued to an AFM probe, preventing adhesion of the liquid. 17 Therefore, the special shape of an optimized tip reduces the capillary effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Yang et al reported chemicalmechanical capillarity to design and generate an optimized shape, which made liquids slide off the surface very quickly. Similarly, we may shape the 3D sieve to follow the brachistochrone curve in our future study and further improve the filtration performance 39 .…”
Section: Hydrodynamics Behavior Of the 3d Sievementioning
confidence: 99%